Sensitive and Rapid Flow Injection Amperometric Hydrazine Sensor using an Electrodeposited Gold Nanoparticle Graphite Pencil Electrode. (2nd September 2019) - Teoman, İsmail and Karakaya, Serkan and Dilgin, Yusuf
Abstract: A gold (Au) nanoparticle-modified graphite pencil electrode was prepared by an electrodeposition procedure for the sensitive and rapid flow injection amperometric determination of hydrazine (N2 H4 ). The electrodeposited Au nanoparticles on the pretreated graphite pencil electrode surface were characterized by scanning electron microscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction spectroscopy, and electrochemical impedance spectroscopy. Cyclic voltammograms showed that the Au nanoparticle-modified pretreated graphite pencil electrode exhibits excellent electrocatalytic activity toward oxidation of hydrazine because the highly irreversibly and broadly observed oxidation peak at +600 mV at the pretreated graphite pencil electrode shifted to −167 mV at the Au nanoparticle pretreated graphite pencil electrode; in addition, a significant enhancement in the oxidation peak current was obtained. Thus, the flow-injection (FI) amperometric hydrazine sensor was constructed based on its electrocatalytic oxidation at the Au nanoparticle-modified pretreated graphite pencil electrode. The Au nanoparticle-modified pretreated graphite pencil electrode exhibits a linear calibration curve between the flow injection amperometric current and hydrazine concentration within the concentration range from 0.01 to 100 µM with a detection limit of 0.002 µM. The flow injection amperometric sensor has been successfully used for the determination of N2 H4 in water samples with good accuracy and precision.